(untitled) (Cardiovascular Journal, 2014)
Editor Navin C Nanda Published by Jaypee Brothers Medical Publishers (P) Ltd. Encyclopaedia on Echocardiography DOI: http://dx.doi.org/10.3329/cardio.v6i2.18367 Cardiovasc. j. 2014; 6(2): 189-190